2006
DOI: 10.1088/0953-8984/18/3/014
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering study of the a-GeTe structure and possible mechanism for the amorphous to crystal transition

Abstract: We report on an inelastic (Raman) light scattering study of the local structure of amorphous GeTe films. A detailed analysis of the temperature-reduced Raman spectra has shown that appreciable structural changes occur as a function of temperature. These changes involve modifications of atomic arrangements such as to facilitate the rapid amorphous-to-crystal transformation, which is the major advantage of phase-change materials used in optical data storage media. A particular structural model, supported by pola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
175
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(205 citation statements)
references
References 35 publications
23
175
1
6
Order By: Relevance
“…Reactions performed at 180°C also gave GeTe particles, whose size and shape were comparable to those obtained at 160°C. These findings somehow correlate with those of previous studies, in which the amorphous-to-crystalline phase transition for GeTe thin films was found to occur at 145°C, 53,54 whereas bulk GeTe started to crystallize at roughly 180°C. 55 However, this finding has to be considered as rather coincidentally since the solution-based growth of crystalline GeTe particles kinetically differs from the reorganization of solid GeTe from the metastable amorphous state to the crystalline state.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Reactions performed at 180°C also gave GeTe particles, whose size and shape were comparable to those obtained at 160°C. These findings somehow correlate with those of previous studies, in which the amorphous-to-crystalline phase transition for GeTe thin films was found to occur at 145°C, 53,54 whereas bulk GeTe started to crystallize at roughly 180°C. 55 However, this finding has to be considered as rather coincidentally since the solution-based growth of crystalline GeTe particles kinetically differs from the reorganization of solid GeTe from the metastable amorphous state to the crystalline state.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…51,52 Based on experimental and theoretical studies, it has been suggested that a-GST is characterized by the presence of fourfold coordinated Ge atoms, 37,42,46,48,50,[53][54][55][56][57][58][59][60] in which the sum of the occurrences of GeTe 4 , Ge͑SbTe 3 ͒, and Ge͑GeTe 3 ͒ is about 66%, 59 which is similar to the local environments observed in amorphous GeTe for GeTe 4 and Ge͑GeTe 3 ͒. 61 Ge-Ge and Ge-Sb bonds are found in those motifs, which is assumed to be due to disorder effects, since they are not present in the crystalline phases. Furthermore, a-GST shows volume expansion of 6%-7% compared with the m-GST phase, 10,36,62 and it has a higher energy ͑28-40 meV/at.͒ with respect to m-GST.…”
Section: Introductionmentioning
confidence: 73%
“…For all the Raman spectra, there are peaks found at 88, 120, 139, and 160 cm -1 . The broad peaks found at 88 and 160 cm -1 are contributed by GeTe vibration modes [14,34,35]. Two distinct peaks were also observed at 120 and 139 cm -1 , and their intensities decreased with increasing deposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were excited with a He-Ne laser (k = 633 nm), and the incident laser power was adjusted to 0.5 mW in order to minimize heating effects in the illuminated sample region of interest [9,14]. The Raman spectra were recorded at an interval of 0.4 cm -1 .…”
Section: Methodsmentioning
confidence: 99%